Web-Integration - Arysbaev, Арсен (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
This article discusses the key aspects of WEB integration, its types and approaches, as well as their advantages from a technical and business point of view. The question of the relevance and role of WEB integration and WEB services in modern times, as well as their advantages. Two main types of integration are analyzed. The positive aspects and advantages of WEB integration from a business perspective are substantiated and listed. The main approaches that are used for WEB-integration are analyzed: integration at the presentation level, integration at the functionality level, integration at the data level and integrated integration. The situations and applications of each of the above types of WEB integration are described, as well as the possibilities they provide for various situations. The analysis and comparison of the main types of WEB integration is carried out and examples based on the integration of social networks are given, namely, the integration of social networks on the site, which is one of the most effective ways of integration in order to expand audience coverage, simplify and interact with the user. The following examples of integrating social networks into a website are considered: adding “Share” and “Like” buttons to enable users to respond to and share other users’ content; the embedding of social media content, which makes it possible to embed posts from social networks directly on the site; using the API to obtain user data. The results of the research and conclusions on the relevance of WEB integration and its role in the modern world are presented.